Evaluation of the functional state of taekwondo athletes 7-13 years old according to the indicators of the finger-tapping test - Olha Podrihalo; Vyacheslav Romanenko; Leonid Podrigalo; Sergii Iermakov; Oleh Оlkhovyi; Anastasiia Bondar; Alla Semyzorova; Volodymyr Galimskyi (Kharkiv State Academy of Physical Culture, 2023)
Background and Study Aim. The functional state of organs and systems determines the level of preparedness of athletes in modern sports. The evaluation of the state of the central nervous system is of particular importance. The purpose of the study is a comparative analysis of the results of the tapping test of taekwondo athletes of different ages. Material and Methods. 42 taekwondo athletes were divided into groups of 14 people depending on age: group 1 - (7.50±0.14) years, group 2 - (10.07±0.22) years, group 3 - (13.36±0.27) years. Participants of groups 1 and 2 were engaged in the amateur level, and group 3 had a skill level of 2 Gup - 1 Dan. A special computer program for devices with the iOS operating system was used. An Apple tablet was used - iPad, 4th generation with a screen diagonal of 9.7 inches. The finger-tapping test was carried out for 60 s, 12 subtests of 5 s each. For analysis, we evaluated the total number of depressions during the entire test, the average number of depressions per 5 s, the number of depressions in each subtest, the duration of depressions in each subtest, and the dynamic performance index (DPI). Group results were compared using the nonparametric Rosenbaum test (Q) and sign test (z). Results. It was found that the athletes of the 2nd group performed more depressions in the test as a whole and in 11 out of 12 subtests compared with the athletes of the 1st group. Comparison of the middle and senior groups also confirmed the best results of the athletes of the senior group in 6 subtests out of 12. The senior athletes had a longer duration of depressions in 2 subtests. The most pronounced differences were established when comparing the results of the junior and senior groups. A significant excess in the number of depressions was confirmed for senior athletes in all subtests. The duration of depressing was longer in senior athletes in 2 subtests. A significant reduction in the number of depressions from the beginning to the end of the test was determined. Changes in the duration of depressions were opposite, and the time increased from the beginning to the end of the test. Conclusions. The presence of a direct dependence of the results of the finger-tapping test of taekwondo athletes on age is determined. An increase in the number of depressions in the test, an increase in the integral criterion - an indicator of dynamic performance was determined. The results reflect an increase in the strength of nervous processes, positive changes in the functional state under the influence of regular training loads. This condition should be evaluated as a predictor of the success of taekwondo athletes. The computer version of the test is mobile, informative and valid. It can be used in monitoring the functional state of combat sports athletes.